2023
DOI: 10.1111/cns.14289
|View full text |Cite
|
Sign up to set email alerts
|

Mediation effect of stroke recurrence in the association between post‐stroke interleukin‐6 and functional disability

Abstract: AimPost‐stroke inflammation increases the risk of functional disability through enlarged cerebral infarct size directly and follow‐up stroke event indirectly. We aimed to use post‐stroke proinflammatory cytokine interleukin‐6 (IL‐6) as a marker of inflammatory burden and quantify post‐stroke inflammation's direct and indirect effect on functional disability.MethodsWe analyzed patients with acute ischemic stroke admitted to 169 hospitals in the Third China National Stroke Registry. Blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…IL‐6 shows a clear dose–response association with the risk of incident AIS 32 . A previous study showed that over 80% of the functional damage after AIS resulted from perturbations to the IL‐6 pathway, rather than stroke recurrence 33 . As ND is considered to be a predictive factor for long‐term poor outcomes, 7 the correlation between ND and poor long‐term outcomes may result from a prolonged post‐stroke inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐6 shows a clear dose–response association with the risk of incident AIS 32 . A previous study showed that over 80% of the functional damage after AIS resulted from perturbations to the IL‐6 pathway, rather than stroke recurrence 33 . As ND is considered to be a predictive factor for long‐term poor outcomes, 7 the correlation between ND and poor long‐term outcomes may result from a prolonged post‐stroke inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“… 32 A previous study showed that over 80% of the functional damage after AIS resulted from perturbations to the IL‐6 pathway, rather than stroke recurrence. 33 As ND is considered to be a predictive factor for long‐term poor outcomes, 7 the correlation between ND and poor long‐term outcomes may result from a prolonged post‐stroke inflammatory state. IL‐6 signaling mechanisms 34 and levels of hsCRP 35 vary at different phases of an ischemic stroke; therefore, further studies are required to provide clear evidence of inflammatory profiles during admission, hospitalization, and follow‐up to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The modified Rankin Scale (mRS) was used to evaluate the functional outcomes in the 3 months after IS. A lower mRS score (0-2) indicates a better functional outcome (n = 3741), and a higher score (3)(4)(5)(6) indicates an adverse functional outcome (n = 2280). This study used the results adjusted for age, gender, ancestry, and baseline stroke severity for the primary MR analysis.…”
Section: Gwas Data Of Functional Outcomes Following Ismentioning
confidence: 99%
“…Aside from traditional risk factors such as blood pressure, smoking, and sleep [3][4][5], as an indispensable part of the pathophysiology of stroke, inflammation assumes a pivotal role in the pathogenesis and prognosis of the disease [6]. Several cytokines and growth factors are involved in the regulation of inflammatory responses [7].…”
Section: Introductionmentioning
confidence: 99%